438 Appearances are deceiving. (8th December 2021) - Conti, Valentina; Moretti, Claudio; Rovera, Chiara; Franco, Erica
Abstract: Aims: Mitral valve prolapse (MVP) is frequently found in the population (3% prevalence). MVP prognosis is generally benign; however, malignant arrhythmias and increased risk of arrhythmic sudden cardiac death (0.2% to 0.4% per year) was described in patients, usually female, mostly affected by bileaflet myxomatous disease, mid-systolic click, ripolarization abnormalities in the inferior leads, and complex ventricular arrhythmias with polymorphic/right bundle branch block morphology, without significant regurgitation. The actual burden, risk stratification, and treatment of the so-called arrhythmic MVP are unknown. Methods: Z.T. is a 32 years old woman who was admitted to the Emergency Department (ED) with left arm and face paraesthesia. She also reported having suffered from migraine and hypertension a few days earlier. ECG: normal sinus rhythm, no ripolarization abnormalities. CT and MRI were executed to rule out cerebral ischaemic events and both resulted negative. No SCD was reported in the anamnesis and the patient denied syncopal and pre-syncopal episodes. Z.T. had undergone cardiologic examination for tachycardia 2 years before the present events, during her second pregnancy (she produced no documentation to this effect). No chronic therapy. Low blood pressure at home. Due to the patient's cardiologic history, ECG monitoring was performed, evidencing frequent premature ventricular beats (PVBs), some couples, and triplets. Cardiologic evaluation was requested. On Echocardiogram: Normal bi-ventricular function. Bileaflet mitral valve prolapse with myxomatous degeneration. Minimal valve regurgitation. Mitral annulus disjunction. TE echocardiogram: no PFO. Nadolol 20 mg was prescribed and after 24 h of observation the patient was discharged, scheduling Holter ECG, cardiac MRI and arrhythmologic evaluation. Results: One month later, the patient reported intolerance to nadolol due to hypotension and pre-syncopal episodes during postural changes. Holter ECG revealed: polymorphic PVBs (2009), couples (383), triplets (40). Cardiac MRI: mitral valve prolapse (11 mm), mitral annulus disjunction (8mm) systolic curling (3mm). No LGE. No oedema. Nadolol was discontinued and substituted with bisoprolol 2.5 mg. Physical activity was discouraged; Ergometric test and Holter ECG were ordered under treatment with bisoprolol. The Ergometric test revealed reduced extrasystolia during physical effort, isolated PVBs and some couples during recovery. Holter ECG revealed continuing isolated PVBs (980) and some couples (37). No complex arrhythmia. Conclusion: Z.T. is affected by an arrhythmic MVP syndrome characterized by complex PVBs, mitral annular disjunction, and systolic curling, which have been described by pathological and cardiac magnetic resonance studies in sudden death victims. However, Z.T. is asymptomatic: no ECG ripolarization abnormalities at rest and good response to medical therapy with β-blockers. Our patient strategy was conservative and we decided to follow up with trimestral cardiologic evaluation and Holter ECG. Further research is needed to best identify high-risk patients and suggest treatments aimed to prevent sudden death.